Core Training Model Using Swiss Ball Based on Interactive Multimedia for Pencak Silat Athletes Aged 15-17 Years Students - Asmutiar; dani, Ramdani Amrullah; Aji, Tri (Journal of Physical Education and Sports, 2024)
Core muscles are very important for stabilization and building strength in all sports activities. This study aims to develop an interactive media design model as a source of exercise and to determine the effectiveness of the core exercise model based on interactive media using a Swiss ball on student athletes. Method: This study uses research and development, validity test of questionnaire conducted by experts in their field. Testing the ability of the product produced, using the design of experimental quesi done with the model Pretest-Posttest Control Group Design. The number of samples used as many as 60 athletes aged 15-17 years, divided into 30 experimental classes and 30 controls. Data analysis test the effectiveness of media training intractive developed using t test Increase the exercise results of athletes using Gain Score. Analysis: the average N-gain score for the experimental group obtained a value of 58 included in the category of quite effective, with a minimum N-gain score value of 19.53 with a maximum value of 200 while the N-gain score for the control class (conventional exercise model) is 25.4 included in the category of “less effective”, with a minimum N-gain score value of 0.89 and a maximum N-gain value of 89.58. So it can be concluded that the core exercises using swiss ball are quite meaningful from the conventional exercise model. Conclusion: Based on the pretest and posttest evidence, core exercises using Swiss ball based on interactive media effectively increase core muscle strength. The effectiveness of core exercises based on Swiss ball must be accompanied by a training pattern that suits the muscle group and anatomical adaptation of the exercise according to the athlete’s ability.